Primera experiencia de criobiopsia transbronquial para enfermedad pulmonar intersticial difusa en un hospital nacional de Lima, Perú - Mendoza, Jorge R. (2024)
Transbronchial cryobiopsy has been described as a new method to obtain lung tissue, demonstrating good correlation with surgical lung biopsies, fewer complications, costs and hospital stay. We describe our first experience carried out successfully in a national hospital. This is a 53-year-old female patient, with a disease duration of five years, characterized by progressive dyspnea. Non-UIP standard tomography. Rheumatological study: mixed positive ANA, speckled nuclear 1/2560 and nucleolar 1/5120. Anti-ENA positive, ANCA negative. Spirometry with FVC 1.83 (69%) and diffusion test 10.39 (67%). After the evaluation of the multidisciplinary committee, a lung biopsy was indicated. After clinical and functional evaluation, cryobiopsy was performed with the use of general anesthesia, prophylactic endobronchial blocker, fluoroscopic guidance and cryoprobe.